2017
DOI: 10.5209/esmp.58027
|View full text |Cite
|
Sign up to set email alerts
|

China tras la mirada de la televisión española

Abstract: Recibido: 18 de noviembre de 2016 / Aceptado: 7 de marzo de 2017 Resumen. La movilidad psíquica que proporcionan los medios permite disponer de una imagen de un país en el que no se ha estado o de una sociedad con la que no se mantiene relación directa. Esta imagen construida se asienta sobre intereses editoriales y simplificaciones productivas que responden a la posición que ocupa el país en relación a otros. En el caso de China se observa en la televisión cómo las informaciones políticas y económicas cara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Chinese media in Kenya and South Africa were found to generate little impact on audiences’ perception of China—most still harbor negative attitudes (Wasserman and Madrid-Morales, 2018). Likewise, Rodríguez Wangüemert et al (2017) studied broadcast news in Spanish media and found that China has been treated as a peripheral country and often framed with a threat and confrontation undertone. Given the above evidence, we posit the following question:RQ1: How has the Latin American press covered China in terms of topics, tones, and frames during the period of the Belt and Road Initiative?…”
Section: Mediated China In Latin Americamentioning
confidence: 99%
“…Chinese media in Kenya and South Africa were found to generate little impact on audiences’ perception of China—most still harbor negative attitudes (Wasserman and Madrid-Morales, 2018). Likewise, Rodríguez Wangüemert et al (2017) studied broadcast news in Spanish media and found that China has been treated as a peripheral country and often framed with a threat and confrontation undertone. Given the above evidence, we posit the following question:RQ1: How has the Latin American press covered China in terms of topics, tones, and frames during the period of the Belt and Road Initiative?…”
Section: Mediated China In Latin Americamentioning
confidence: 99%